The presentation of the orphan child in eighteenth and early nineteenth century English literature in a selection of William Blake's 'Songs of innocence and experience', and in Charlotte Brontë's 'Jane Eyre', and Emily Brontë's 'Wuthering Heights' - Singh, Jyoti (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2010)
This thesis is a study of the presentation of the orphan child in eighteenth and early nineteenth century English literature, and focuses on William Blake's Songs of Innocence and Experience, Charlotte Bronte's Jane Eyre, and Emily Bronte's Wuthering Heights. It is concerned with assessing the extent to which the orphan children in each of the works are liberated from familial and social constraints and structures and to what end. Chapter One examines the major thematic concern of the extent to which the motif of the orphan child represents a wronged innocent, and whether this symbol can also, or alternatively, be presented as a revolutionary force that challenges society's status quo in Blake's Songs of Innocence and Experience. Chapter Two considers the significance of the child "lost" and "found", which forms the explicit subject of six of Blake's Songs of Innocence and Experience and explores the treatment of these conditions, and their differences and consequences for the children concerned. Chapter Three focuses on Charlotte Bronte's depiction of the orphan in Jane Eyre, which presents two models of the orphan child: the protagonist Jane, and Helen Burns. The chapter examines these two models and their responses to orphan-hood in a hostile world where orphans are mistreated by family and society alike. Chapter Four determines whether the orphan constitutes a subversive threat to the family in Emily Bronte's Wuthering Heights and also explores the notion that, although orphan-hood often entails liberation from adult guardians, it also comprises vulnerability and exposure. The thesis concludes by considering the extent to which orphan-hood can involve a form of liberation from the confines of social structures, and what this liberation constitutes for each of the three authors.
Keywords: Blake, William, 1757-1827 -- Songs of innocence and of experience -- Characters -- Orphans; Blake, William, 1757-1827 -- Criticism and interpretation; Brontë, Charlotte, 1816-1855 -- Jane Eyre -- Characters -- Orphans; Brontë, Charlotte, 1816-1855 -- Criticism and interpretation; Brontë, Emily, 1818-1848 -- Wuthering Heights -- Characters -- Orphans; Brontë, Emily, 1818-1848 -- Criticism and interpretation; Orphans in literature